Google Sites for Science Education: Navigating Challenges and Embracing Opportunities - Haerul Johdi; Gunawan Gunawan; Lovy Herayanti (Indonesian Publication Center, 2025)
This study investigates the integration of Google Sites as a digital learning platform in science education, specifically examining the prevailing challenges and pedagogical opportunities. Utilizing a systematic literature review of ten peer-reviewed articles, the research analyzes the platform's efficacy in enhancing conceptual understanding, scientific process skills, and problem-solving abilities. The findings indicate that Google Sites serves as a versatile and interactive medium capable of accommodating diverse instructional materials and learning styles. Evidence suggests a positive correlation between platform implementation and increased student engagement and motivation. However, critical barriers persist, including the necessity for specialized teacher professional development in digital content curation and the requirement for robust technological infrastructure. The study concludes that while Google Sites offers significant potential for innovation in science pedagogy, its success is contingent upon strategic planning and sustained institutional support to ensure long-term educational quality.